Benzimidazole-heterocyclic hybrids as potential anticancer agents: A review on outstanding research - Em, Pham Canh (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2021)
Cancer is one of the most serious medical problem and second leading cause of death in the world, characterized by a deregulation of the cell cycle which mainly results in a progressive loss of cellular differentiation and uncontrolled cellular growth. Benzimidazole-heterocyclic hybridization, involving a combination of benzimidazole nucleus and other pharmacophores of bioactive heterocyclic scaffolds to generate a single molecular architecture with improved affinity and activity, in comparison to their parent molecules, has emerged as a promising strategy in recent drug discovery research. Hybrid anticancer drugs are of great therapeutic interests since they can potentially overcome most of the pharmacokinetic drawbacks encountered with conventional anticancer drugs. Strategically, the design of anticancer drugs involved the blending or linking of an anticancer drug with another anticancer drug or a carrier molecule which can efficiently target cancer cells with improved biological potential. Major advantages of hybrid anticancer drugs involved increased specificity, better patient compliance, and lower side effects along with reduction in chemo-resistance. This review is intended to provide an overview of discovery and development in benzimidazole-heterocyclic anticancer hybrids, as well as inspire the design and synthesis of new anticancer molecules.